Pertentangan Antara Literasi Kesehatan Seksual Dan Pemali: Deskripsi Pada Remaja Di Desa Ayula Selatan - La Ode Gusman Nasiru; Gita Juniarti; Waode Mustika (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2026)
This study analyzes the management of sexual health information among adolescents in Ayula Selatan Village, Gorontalo, amidst the challenges of social taboos, conservative values, and vulnerability to myths. The Elaboration Likelihood Model (ELM) was used in this study. The purpose of this study is to identify the message processing pathways, i.e. central or peripheral pathways, used by adolescents. This study adopted a mixed methods method with an explanatory sequential design to complete the analysis in this study. Quantitative data from 76 respondents measured adolescents' understanding of sexual health myths and facts, combined with in-depth interview data from selected respondents. The results showed an imbalance in adolescents' knowledge about myths and facts related to sexual health. In addition, information about sexual health tends to be obtained from digital media without assistance from parents or teachers. A sense of taboo and embarrassment to ask questions is one of the reasons why adolescents discuss with peers rather than adults. Another interesting finding shows that adolescents also discuss with artificial intelligence to validate their knowledge about sexual health. ELM analysis found that the majority of adolescents used peripheral pathways in this study. They accepted messages based on non-message cues such as influencer popularity, language style and aesthetic visualization. The adolescents disregarded the quality of arguments. The dominance of this pathway has consequences in the form of temporary changes in attitudes and the risk of spreading misinformation. This study suggests designing adaptive educational programs and strengthening the role of family and school as credible sources.